2012
DOI: 10.1530/jme-12-0195
|View full text |Cite
|
Sign up to set email alerts
|

hCG-induced endoplasmic reticulum stress triggers apoptosis and reduces steroidogenic enzyme expression through activating transcription factor 6 in Leydig cells of the testis

Abstract: Endoplasmic reticulum (ER) stress generally occurs in secretory cell types. It has been reported that Leydig cells, which produce testosterone in response to human chorionic gonadotropin (hCG), express key steroidogenic enzymes for the regulation of testosterone synthesis. In this study, we analyzed whether hCG induces ER stress via three unfolded protein response (UPR) pathways in mouse Leydig tumor (mLTC-1) cells and the testis. Treatment with hCG induced ER stress in mLTC-1 cells via the ATF6, IRE1a/XBP1, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 44 publications
0
57
0
Order By: Relevance
“…The UPR is crucial for the function of secretory cells, including β cells, hepatocytes, and osteoblasts (Gass et al, 2004; Wu and Kaufman, 2006; Volchuk and Ron, 2010), all of which have heavy protein synthesis demands and thus rely on the proper function of the ER in order to maintain secretory output. It has also been recently described in the Leydig cell where UPR induction causes a decrease in steroid output through activation of the ATF6 pathway and ER stress-mediated apoptosis (Park et al, 2013). …”
Section: Control Of Mrna Translationmentioning
confidence: 99%
“…The UPR is crucial for the function of secretory cells, including β cells, hepatocytes, and osteoblasts (Gass et al, 2004; Wu and Kaufman, 2006; Volchuk and Ron, 2010), all of which have heavy protein synthesis demands and thus rely on the proper function of the ER in order to maintain secretory output. It has also been recently described in the Leydig cell where UPR induction causes a decrease in steroid output through activation of the ATF6 pathway and ER stress-mediated apoptosis (Park et al, 2013). …”
Section: Control Of Mrna Translationmentioning
confidence: 99%
“…However, hCG has higher in vitro activity than LH in terms of cAMP production (28). Moreover, Park and coworkers have recently demonstrated that hCG induces steroidogenic enzyme in vivo in male mice and in vitro in mouse Leydig tumor cells (mLTC-1) (29). In particular, in vitro, after multiple injection of hCG, mRNA levels of steroidogenic enzymes (STAR, 3βHSD, CYP17, and 17βHSD) decreased markedly in mLTC-1 cells (29).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Park and coworkers have recently demonstrated that hCG induces steroidogenic enzyme in vivo in male mice and in vitro in mouse Leydig tumor cells (mLTC-1) (29). In particular, in vitro, after multiple injection of hCG, mRNA levels of steroidogenic enzymes (STAR, 3βHSD, CYP17, and 17βHSD) decreased markedly in mLTC-1 cells (29). Similarly, in vivo models show an increased production of mRNA and proteins of 3βHSD, P450c17, and 17βHSD3 during the first 12 h after daily hCG treatment (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LH induces T production in testicular Leydig cells. Exogenous hCG acts similar to LH through the same LH receptor (LHR) (Saez, 1994; Park et al ., 2013). In Leydig cells, LH or HCG binds to LHR to activate adenylyl cyclase and convert ATP into cAMP.…”
Section: Introductionmentioning
confidence: 99%